Letters of the law : the trial of E. K. Avery for the murder of Sarah M. Cornell - J. Barbour (Law Text Culture, 1995)
The district attorney [prosecuting a murder in USA 1900] said that it was difficult to assemble a jury "owing to the notoriety and publicity which has been given to the case and to the fact that it has been widely commented on". Television may have made it almost impossible to find a jury for O. J. Simpson, but before TV there was the cigar store (London Review of Books, 20 April 1995: 4). The case In Newport Rhode Island in the summer of 1833, a minister of the Methodist Episcopal Church, Ephraim Kingsbury Avery, was tried for the murder of a mill-worker, Sarah Maria Cornell, in the small settlement of Fall River, near the Rhode Island-Massachusetts border. The case had wide publicity coverage, and set judicial precedents: forty eight jurors were challenged before twelve were empannelled; the trial took over four weeks (7 May to 6 June) instead of the usual two at most; the defense called dozens of witnesses, at one point bunching nine women character witnesses (all unfavourable to Cornell), and at another seven men who provided minute-by-minute alibis for Avery (Kasserman 1986: 169), to make a cumulative 'serial' effect on the jury. It recalled numbers of prosecution witnesses to the stand for aggressive cross-examination, and managed to shake the prosecution's most important eye-witness identification of Avery. Even the charges against Avery were awkwardly framed, perhaps designedly to cover doubts as to whether the cause of death was from being bashed, strangled or hanged, or perhaps to preempt the claim that Cornell had suicided; all of these explanations were favoured in some quarters.